Hybrid modelling for supervisory control purposes for the brine heater of a multi stage flash desalination plant - Gambier, Adrián; Fertig, Matthias Wilhelm; Badreddin, Essameddin (ACC, 2002)
Multistage flash desalination is the most common process to produce freshwater from seawater based on large scale distillation. The process is energy intensive but essential for the maintenance of life support in regions with scarcity of water resources. Such plants need an efficient control system in order to be economically viable. A hybrid model for supervisory control purposes based of a hybrid automaton is proposed in this contribution.
Gesehen am 14.01.2020